Some issues regarding the financing of family foster care - Łakoma, Sylwia (Studia Iuridica Toruniensia, 2023)
The aim of this paper is to discuss the financing of family foster care from a legal perspective. This subject has been chosen considering the importance of this form of foster care in the life of a child deprived of parental care. In view of the foregoing, it is impossible to ignore one important factor which contributes significantly to the proper functioning of family foster care, thus enabling it to fulfil the role ascribed to it. The factor in question is financial support for family foster care and, more specifically, for foster families (related, non-professional, professional, including specialist ones) and family children’s homes, which are its components. Considering the above, this paper attempts to show the relation and unquestionable interdependence between the proper functioning of family foster care and selected financial benefits, which, as a rule, are payable for fulfilling the function of a foster family or running a family children’s home.